Pendekatan Konseling "Trait and Factor" sebagai Upaya Meningkatkan Perencanaan Karir Siswa MAN 1 Surakarta - Febriansyah, Bilal Eleazar; Ali, Mohammad (Instructional Development Journal, 2025)
Career planning is an important aspect in students' lives, especially in secondary education. One approach that can be used to help students plan their careers is Trait and Factor counseling. This study aims to examine the effectiveness of the Trait and Factor counseling approach in helping MAN 1 Surakarta students plan their careers. The method used in this study is qualitative with a case study approach. Data were collected through interviews, observations, and documentation which were then analyzed descriptively. The results showed that the Trait and Factor approach was able to increase students' awareness of their interests, talents, and existing job opportunities.